HtrA3 paves the way for MSC migration and promotes osteogenesis - Yaru Guo; Siqin Ma; Dandan Wang; Feng Mei; Yusi Guo; Boon Chin Heng; Shihan Zhang; Ying Huang; Yan Wei; Ying He; Wenwen Liu; Mingming Xu; et al. (Bioactive Materials, 2024)
Mesenchymal stem cell (MSC) migration determines the healing capacity of bone and is crucial in promoting bone regeneration. Migration of MSCs is highly dependent on degradation of extracellular matrix by proteolytic enzymes. However, the underlying mechanisms of how enzymolysis paves the way for MSCs to migrate from their niche to the defect area is still not fully understood. Here, this study shows that high-temperature requirement A3 (HtrA3) overcomes the physical barrier and provides anchor points through collagen IV degradation, paving the way for MSC migration. HtrA3 is upregulated in MSCs at the leading edge of bone defect during the early stage of healing. HtrA3 degrades the surrounding collagen IV, which increases the collagen network porosity and increases integrin β1 expression. Subsequently, integrin β1 enhances the mechanotransduction of MSCs, thus remodeling the cytoskeleton, increasing cellular stiffness and nuclear translocation of YAP, eventually promoting the migration and subsequent osteogenic differentiation of MSCs. Local administration of recombinant HtrA3 in rat cranial bone defects significantly increases new bone formation and further validates the enhancement of MSC migration. This study helps to reveal the novel roles of HtrA3, explore potential targets for regenerative medicine, and offer new insights for the development of bioactive materials.